2019
DOI: 10.1002/evl3.124
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic paternal effects via seminal fluid

Abstract: Mounting evidence suggests that nongenetic paternal effects on offspring may be widespread among animal taxa, but the mechanisms underlying this form of nongenetic inheritance are not yet fully understood. Here, we show that seminal fluids underlie paternal effects on early offspring survival in an insect, the cricket Teleogryllus oceanicus, and quantify the contribution of this paternal effect to the inheritance of this important fitness trait. We used castrated males within a full‐sib half‐sib experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 64 publications
6
43
0
Order By: Relevance
“…In that study, the seminal fluid of some donors was found to enhance embryo viability while the seminal fluid of others reduced embryo viability. Importantly, increasing expression of ToSfp011 in the accessory glands of seminal fluid donors was associated with reduced embryo survival [19]. Taken together with the findings of our interference RNA, the data suggest that while ToSfp011 is essential for embryo development it may be harmful when abundant.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In that study, the seminal fluid of some donors was found to enhance embryo viability while the seminal fluid of others reduced embryo viability. Importantly, increasing expression of ToSfp011 in the accessory glands of seminal fluid donors was associated with reduced embryo survival [19]. Taken together with the findings of our interference RNA, the data suggest that while ToSfp011 is essential for embryo development it may be harmful when abundant.…”
Section: Discussionsupporting
confidence: 67%
“…Using interference RNA, we found that at least one seminal fluid protein, ToSfp011, was essential for the development of embryos to hatching. In a previous study, we documented significant variation in embryo viability among genetically monogamous females mated to castrated seminal fluid donors [19]. In that study, the seminal fluid of some donors was found to enhance embryo viability while the seminal fluid of others reduced embryo viability.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Laboratory studies have examined within‐population variation of SFPs at sequence, expression and functional levels, and established that these proteins exhibit a wide range of functions, such as inducing ovulation or defending mating partners against sexually transmitted diseases (Gioti et al., 2012; McGraw, Clark, & Wolfner, 2008; Peng, Grassl, Millar, & Baer, 2016, review: Avila, Sirot, LaFlamme, Rubinstein, & Wolfner, 2011; Chapman, 2001; Morrow & Innocenti, 2012; Poiani, 2006; Sirot, Wong, Chapman, & Wolfner, 2015). In addition to their immediate effects, SFPs may also be responsible for seminal fluid‐mediated transgenerational effects (Bromfield et al., 2014; Crean, Kopps, & Bonduriansky, 2014; Priest, Roach, & Galloway, 2008; Simmons & Lovegrove, 2019). Moreover, although some effects of SFPs are essential and beneficial for both parents, other functions appear sexually antagonistic (Chapman, Liddle, Kalb, Wolfner, & Partridge, 1995; Patlar, Weber, Temizyürek, & Ramm, 2020, review: Sirot et al., 2015).…”
Section: Introductionmentioning
confidence: 99%